2013
DOI: 10.1093/bja/aes383
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound visual image-guided vs Doppler auditory-assisted radial artery cannulation in infants and small children by non-expert anaesthesiologists: a randomized prospective study

Abstract: US-guided radial arterial cannulation in infants and small children provided a greater chance for success at the first attempt compared with the Doppler-assisted technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 15 publications
3
42
1
1
Order By: Relevance
“…These studies reported final success rates of 65 to 100% for ultrasound-guided techniques. 3,[12][13][14] In this study, the final success rate ranged between 88 and 100%, in agreement with the results of earlier studies and demonstrating a relatively high performance in infants, regardless of the ultrasound-guided arterial cannulation technique used.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These studies reported final success rates of 65 to 100% for ultrasound-guided techniques. 3,[12][13][14] In this study, the final success rate ranged between 88 and 100%, in agreement with the results of earlier studies and demonstrating a relatively high performance in infants, regardless of the ultrasound-guided arterial cannulation technique used.…”
Section: Discussionsupporting
confidence: 91%
“…14 Previous studies on ultrasoundguided arterial cannulation have shown a diverse range of operators' skill: some restricted operators of ultrasound-guided arterial cannulation to those experienced in its use, 3,10,12 and others did not. [13][14][15] The guidelines published by The Royal College of Radiologists recommended that more than 20 ultrasound-guided vascular access attempts in adults are needed for an operator to be competent. 16 Regarding the small vessel sizes in children, operator experience may play a critical role in successful cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…Of 95 potentially relevant articles identified initially, six were included in the meta-analysis [2-7]. An additional RCT was identified from the references [8].…”
Section: Resultsmentioning
confidence: 99%
“…However, several differences should be highlighted here. First, our meta-analysis specifically focused on ultrasound guidance vs. traditional palpation for radial artery catheterization and thus Ueda et al's study [27] comparing ultrasound guidance with Doppler-assisted technique was excluded, which was included in Gu et al's meta-analysis [26]. In addition, our meta-analysis included the most recently published RCT by Hansen et al in 2014 [12], which was not included in Gu et al's [26].…”
Section: Discussionmentioning
confidence: 99%